STRATEGY FOR ADMISSION OF NEW STUDENTS IN INCLUSION SCHOOL AT SCHOOL OF HUMAN JATISAMPURNA BEKASI - Widya Rahmawati Al-Nur (Mozaic : Islam Nusantara, 2023)
This research discusses the strategy of admitting new students at the School of Human (SOH), which is an inclusive school. The purpose of this research is to be able to describe the process of admitting new students to the school where the concept uses a pulse, meaning that all students can enter and attend school at SOH as long as there is still a new student enrollment quota.This research method is descriptive qualitative which presents in full the stages of admitting new students using the pulse method at SOH. The collection of data used is by interviews and documentation related to the acceptance of new students. Data analysis techniques using research data triangulation.In the research on the strategy of admitting new students to SOH without discriminating, it means that all students can become SOH students as long as there is an available quota. As an inclusive school, SOH implements three important stages in admitting new students, namely initial observation which contains general registration, further observation for special students, and class determination using the Multiple Intelligences Research (MIR) method.